Formation of surface layer quality under abrasive treatment of polymer-composite materials - M. A. Tamarkin; Eh. Eh. Tishchenko; A. V. Verchenko; V. M. Troitskii (Advanced Engineering Research, 2020)
Introduction. The study results of the abrasive processing of parts made of polymer-composite materials are presented. The features of processing polymer composites and the technology of preforming through waterjet cutting are described. The stages of preparation of a part made of polymer-composite material for the “glueing” operation are investigated.Materials and Methods. Dependences for determining the surface roughness under waterjet cutting of polymercomposite material are considered. Research is carried out to achieve the required surface roughness under adhesive bonding of workpieces. The dependence is given that describes the roughness that is required for a reliable adhesive bond.Results. The theoretical and experimental studies of the waterjet cutting process are resulted. Their implementation technique, the tool and equipment used are described. The results of theoretical and experimental studies are compared. Their high convergence is established. The results of experimental studies on the preparation of parts made of polymercomposite materials for glueing are shown. The abrasive tools and processing modes are selected.Discussions and Conclusions. The process design procedure of abrasive treatment of workpieces from polymercomposite materials is proposed.